ANALISIS PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP ROFITABILITAS (STUDI PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018) - Saraswati; Manullang, Rizal Ruben; Tri Setyo Mulyani, Hendarti (Jurnal Akuntansi Bisnis Dan Keuangan, 2020)
The purpose of this study is to evaluate and analyze current ratios, debt to equity ratios, total assets, net profit margins and company size to equity returns on pharmaceutical companies listed on the Indonesia Stock Exchange in 2014-2018. A sample of 9 pharmaceutical companies. The sample collection method is purposive sampling. Research is quantitative. Data analysis techniques are descriptive analysis, multiple linear analysis, classic assumption test, coefficient of determination and hypothesis testing. Analyzing using the JASP 0.9.2.0 Universiteit-van-amsterdam application. Simultaneous current ratios, debt to equity ratio, total asset turnover, company size and net profit margins affect the return on equity. Partially the current ratio and company size do not affect the return on equity while the debt to equity ratio, total assets change and net profit margins affect the return on equity.